TRUE LEFT-SIDED GALLBLADDER (T-LSG) AS INCIDENTAL FINDING ON LAPAROSCOPIC CHOLECYSTOMY – CASE REPORT - Gelevski, Radomir; Jota, Gjorgi; Todorovic, Lazar; Trajkovski, Gjorgi; Joksimovic, Vladimir; Trencic, Bojan; Ognjenovic, Ljubomir (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Left-sided gallbladder, located medially to the falciform ligament, between segment III and IV of the liver, has complex embryological development explained by two different concepts: one founded upon foetal migration of the gallbladder; and the other founded upon complex foetal evolution of intrahepatic anatomy. 57-year-old male was admitted for elective cholecystectomy, and, after pneumoperitoneum was established, a true left-sided gallbladder was identified. The patient was positioned in normal position and ports were placed on typical sites. After diligent dissection, cystic artery and duct were clipped as close as possible to gallbladder and dissected. During standard dissection in laparoscopic cholecystectomy, special attention was dedicated to obtaining posterior critical view of safety, providing adequate exposition of structures of Calot’s triangle. Posterior critical view of safety in left-sided gallbladder exposes cardinal structures of hepatic hilus. Although, during laparoscopy, difficult anatomy is met and there is high probability of bile duct injury, laparoscopic cholecystectomy is the recommended procedure of choice for left-sided gallbladder. Key words : left-sided gallbladder, posterior critical view of safety . https://doi.org/10.55302/JMS2141050g